2005
DOI: 10.1094/1891127403
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Flour Milling

Abstract: Like most websites we use cookies. This is to ensure that we give yo possible.Continuing to use www.cabdirect.org means you agree to our use o to, you can learn more about the cookies we use.Abstract : T his book with 16 chapters brings together many ideas and new approaches to theory and practice in wheat flour milling. T he following topics discussed: wheat as a raw material, the flour milling laboratory, wheat storag blending, wheat cleaning and conditioning, grinding, sieving, purification, mill handling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(192 citation statements)
references
References 0 publications
3
181
0
8
Order By: Relevance
“…This is similar to North American hard wheat mills that produce a ratio of patent to clear flour for different price considerations (9). In the case of debranning, the ability to designate and maintain high-value flour products that can be sold at a premium price affects the economic benefits derived through careful operation of a mill to obtain the best possible separation of endosperm from nonendosperm components.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This is similar to North American hard wheat mills that produce a ratio of patent to clear flour for different price considerations (9). In the case of debranning, the ability to designate and maintain high-value flour products that can be sold at a premium price affects the economic benefits derived through careful operation of a mill to obtain the best possible separation of endosperm from nonendosperm components.…”
Section: Resultsmentioning
confidence: 94%
“…However, a significant capacity increase in existing mill equipment, with appropriate changes in the flow sheet, can result in a reduction in energy costs (kWhr/ton of wheat) with use of prebreak debranning. Hard wheat milling is one area in which adaptation of the milling system to debran the wheat grain prior to milling is an option that reportedly results in a practical economic pay back (9). The ideal debranning operation in hard wheat milling would evenly remove the outer layers of the pericarp without removing any endosperm or breaking kernels.…”
mentioning
confidence: 99%
“…In the second explanation, the epoxy layer changed the rear and the cutting angles of the corrugations making them smoother. In a previous study published (Posner and Hibbs, 2005), authors reported that smooth rollers produce finest particles compared to corrugated rollers. This may explain the high number of particles in the case of the coated rollers compared to the uncoated ones.…”
Section: Numbers Of Particles (N T )mentioning
confidence: 95%
“…In addition, a finer milled product can be achieved by adjusting roller speeds and gaps. Roller machines also generate lower temperatures on the roller surface during milling compared with other types of milling machine (Posner and Hibbs, 2005;Prabhasankar and Rao 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Before milling, physical properties of the tempered kernels were measured using the SKCS. For grinding, the experimental laboratory mill (Ross, Oklahoma City, OK) was used in a flow that consisted of four breaks (BK), one sizing (SIZ), two tailings (T), and five reductions (M) (Posner et al 1997). The Ross mill was chosen in this study as it produced 17 product streams compared with the eight streams produced by the Buhler mill.…”
Section: Wheat Preparation and Milling Processmentioning
confidence: 99%